MOBILE-ASSISTED LANGUAGE ASSESSMENT (MALA): THE ADVANTAGES AND DISADVANTAGES IN ASSESSING EFL ACADEMIC ORAL PRESENTATIONS - Raden Hasby Isnaindy Fasa, - (2022)
The advancement of mobile technologies particularly in online learning settings, has pushed the need to not only identify but also implement the proper assessment practices in online learning settings. Mobile assisted language assessment (MALA) is considered as the current method of assessment that is applicable for online learning settings. Therefore, this study aims to investigate the potentials of MALA implementation in supporting EFL academic oral presentations class and students' perception toward it. The research used a case study design. A group of 10 nursing students joining the Health Care Language Program were selected randomly. Data from observation, document, and the students' interview were analyzed. The results of this study indicated that the implementation of MALA supported academic oral presentation instructional practices such as engaging students in the MALA activities in the academic oral presentation class and engaging the students in responding to the feedback given. The students' views revealed the facilitative features of MALA such as interactivity, flexibility, and the opportunity to monitoring as well as reflecting. This study recommends that continued efforts are needed to investigate the teachers' voice toward this issue.